Improved health-related quality of life in the first year after laparoscopic niche resection: a prospective cohort study. (February 2020) - Stegwee, Sanne I.; Hehenkamp, Wouter J.K.; de Leeuw, Robert A.; de Groot, Christianne J.M.; Huirne, Judith A.F.
Abstract: Objective: To evaluate changes in health-related quality of life (HRQOL) the first year after laparoscopic niche resection. Study design: Prospective cohort study in women with a large niche (residual myometrium thickness <3.0 mm) after caesarean section who underwent laparoscopic niche resection between May 2010 and January 2018. Women were included consecutively. 36-Item Short Form Survey (SF-36) was sent at baseline, three and twelve months postoperatively. All participants that filled out the questionnaire at baseline were included. Physical (PCS) and mental component summary scores (MCS) and scores for subdomains were calculated. Scores were analysed over time using Wilcoxon signed rank test. Results: 146 participants responded to the SF-36 at baseline, of which 129 (88.4 %) responded at three or twelve months follow-up. After three months, median PCS and MCS improved, compared to baseline (p = 0.014 and p = 0.008, respectively). Subdomains physical functioning, bodily pain, general health, vitality, mental health and social functioning improved significantly. At twelve months follow-up, improvement in PCS and MCS did not reach statistical significance (p = 0.053 and p = 0.063, respectively). Subdomains bodily pain (77.6–89.8, p < 0.001), mental health (76–80, p = 0.004) and social functioning (75–87.5, p = 0.016) improved significantly. Women with symptom relief as main goal of the intervention showed larger improvement in PCS than women with distorted anatomy and to restore anatomy as main goal for the intervention (p = 0.001). Conclusion: Laparoscopic niche resection improves HRQOL in women with a large niche in physical and mental domains three and twelve months postoperatively.